Bacterial co-infections in a captive Python bivittatus with septicemia - Abba, Y.; Ilyasu, Y.; M. S. M., Yusof; M. M., Noordin (Usmanu Danfodiyo University, 2016)
This case reports bacterial co-infection in a dead albino python (Python bivittatus). The snake was brought in dead to the Universiti Veterinary Hospital, Universiti Putra Malaysia. Necropsy was conducted and organ samples were sent for virus and bacterial isolation, as well as histopathology. Gross pathological lesions include congestion of the heart, spleen and liver and presence of superficial whitish circumscribed spots in the lungs. Bacterial culture showed the presence of Salmonella enterica ssp arizona, Plesiomonas shigelloides and Enterobacter cloacae. Histopathological evaluation showed evidence of necrosis, degeneration and heterophil infiltration in the liver, kidney, heart and lungs. The snake was diagnosed to have died of bacterial septicemia.